Atypical ear lesion as initial presentation in Hansen disease - Sivaji, Akshaya Rathin; Scaria, Tony Kizhakkemuriyil (International Journal of Research in Medical Sciences, 2023)
Hansen's disease is highly infectious and contagious. This disease in some individuals manifests with subtle symptoms such as isolated lesions like nodules over the ear, polyarthritis etc. These manifestations should be considered for the differential diagnosis of leprosy. We present this case with multiple cutaneous nodules over the helix and lobule of the right ear. A histopathological examination confirmed the diagnosis. Early detection and treatment of this disease prevent further complications.